Determination of dexamethasone sodium phosphate and dexamethasone base in one sample of horse plasma or/and synovial fluid using high resolution liquid chromatography. Technical note - Carballo, Raúl; Rosiles, Rene; Bautista, Juan; Octavio Fuentes, Víctor (Revista Científica de la Facultad de Ciencias Veterinarias, 2012)
Ver resumen pdf.